A Study on Remote Monitoring of NOx Emissions from Inland Vessels - Mengtao Deng; Jianbo Hu; Zhaoyu Qi; Shitao Peng (Remote Sensing)
In order to demonstrate the feasibility of the tunable diode laser absorption spectroscopy (TDLAS) technology for monitoring NOx emissions from inland vessels, an equipment is designed to monitor emissions for inland vessels. The equipment was installed at the Jianbi locks, where experimental measurements were conducted on vessels passing through the locks, with a total of 330 vessels being measured. The detection rate for vessels was 50.3%, with a detection rate of 72.4% for fully loaded vessels and 24.7% for unloaded vessels. In addition, the exhaust emission patterns of inland vessels, the NOx emission patterns and detection rate of fully loaded and unloaded vessels, and the key parameter of the NOx emission factor of inland vessels were comprehensively analyzed. The experimental results show that CO2 and NOx in the exhaust gas of inland vessels have high signal intensity and good synchronization and can be applied to the regulatory monitoring of NOx emissions from inland vessels. Furthermore, the ratios of NO/CO2 and NO2/CO2 from fully loaded and unloaded vessels were significantly different. indicating that the NO2 indicator must be included in the remote monitoring indicators for inland vessel exhaust gases. Otherwise, the remote monitoring results for NOx may be significantly underestimated.